Development of a Diesel Engine Test Technique for Evaluating Arctic Engine Oils. - Lestz,Sidney J. (1973)
An engine test technique was developed for evaluating the performance of sub-zero engine oils in high-output diesel engines. Field tested lubricants were used to develop the laboratory engine performance criteria. Validity of the test procedure is demonstrated by direct laboratory to field correlation. The major areas of test technique development, establishment of performance criteria, lubricant evaluations, and overall lubricant performance are presented and discussed as an integrated effort rather than each as a separate project phase. Illustrations of hardware, including test set-up and test components are included for summary purposes only. Physical and compositional properties of the test development lubricant are discussed which help explain why the engine discriminates lubricant quality under high-output conditions. The test method developed as a result of this work could be used to qualify military arctic engine oil candidates. (Author)